Evaluation of anthelmintic activities of crude leaf extracts of three indigenous herbal plants against ovine gastrointestinal nematodosis - Biftu, D.; Nurfeta, A.; Jobre, Y. (2004)
An experiment was carried out to evaluate anthelmintic activities of three herbal plants, namely; Dodonea viscose, Albizzia gummifera and Veronia amygdalina against gastrointestinal nematode infections in sheeThe experiment was set in a parallel group design (PGD) with five treatment groups each consisting four animals. The first group (G1) was treated with Albendazole (negative control) and the remaining three groups (G2, G3, and G4) received crude extracts of the candidate herbs. The fifth group (G5) was left untreated (positive control). Efficacy of the tested materials was measured based on the significances in the reduction in mean faecal egg count (MFECC) and improvements in mean body weight changes (MBWC) before and after treatments. Albizzia gummifera showed significant (p<O.C05) anthelmintic activities with MFECC (%) of52.2±0.71, and, MBWC (%) of 21.0±1.1. Conversely, no significant (p>0.05) anthelementic activities were observed with Dodonea viscose (MFECC (%)=1.2±0.56, and MBWC =10.2±1.96,P>0.05) and Veronia amygdalina (MFECC (%)=-5.7±0.5 and MBWC (%)4.2±10. Albizzia gummifera was thus proved to bring maximum anthelmintic effects. However, further experiments need to be carried out to determine the optimal curative dose without any untoward toxicity effect on recipient subjects. In addition, it is recommended to evaluate the medicinal effects of the roots and barks of Albizzia gummifera against various species of helminths. This study also revealed that not all herbal plants traditionally used by farmers have anthelmintic effects. Future evaluation of medicinal values of indigenous herbs in Ethiopia is needed and conducted following standard procedures employing both in vitro and in vivo experiments.